Frequency of Vitamin B12 Deficiency Among Patients with Diabetes - Rehman, Fazal Ur; Khan, Khushhal; Ullah, Inam; Mansoor, Javeria; Manzoor, Rida; Khan, Hasil; Raheem, Abdul; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Cobalamin, often known as vitamin B12, is an essential ingredient for DNA synthesis, brain function, and the creation of red blood cells. Metformin is a commonly used first-line treatment for diabetes mellitus (DM), especially type 2 diabetes (T2DM), which is becoming a major worldwide health concern. However, chronic metformin use has been linked to reduced absorption of vitamin B12, increasing the risk of insufficiency in diabetics. Objective: This study aims to determine the frequency of vitamin B12 deficiency among diabetic patients and examine its associations with metformin use, disease duration, dietary habits, and clinical symptoms. Methods: At tertiary care hospital Quetta, 300 patients with diabetes (type 1 and type 2) participated in a qualitative study. Structured interviews, clinical history reviews, and vitamin B12 level analysis of blood samples were all used in the data collection process. Patterns pertaining to metformin use, the length of diabetes, and dietary practices were found using thematic analysis. Results: Patients with long-term diabetes, long-term metformin use, and vegetarian diets were far more likely to have vitamin B12 deficiency. Deficiency rates among metformin users rose from 20% (use <5 years) to 65% (use >10 years). Neuropathy (53.3%), exhaustion (46.7%), cognitive impairment (30%), and anemia (26.7%) were among the most common symptoms. Conclusion: The findings highlight the need for healthcare professionals to monitor vitamin B12 levels in diabetic patients, especially those at higher risk due to prolonged metformin use and dietary restrictions. The study confirms a high prevalence of vitamin B12 deficiency among diabetic patients, especially those on long-term metformin therapy. Early intervention, including dietary modifications and supplementation, and routine screening are crucial to prevent complications like neuropathy and anemia.